Biochemical alteration bovines due to caesarean operation with reference to Suture material and intra-peritoneal libricant - DHINDSA, S S; DHALIWAL, G S; GHUMAN, S P S (The Indian Journal of Animal Sciences, 2011)
The present study ~Ias undertaken in 41 dystocia affected bovines subjected to caesarean operation to assess certain biochemical alterations with reference to type of material (chromic catgut, CC or polyglycolic acid, PGA) used for suturincr uterine incision with or without infusion of an intra-peritoneal lubricant (sodium carboxy methyl cellulose, SCMC)during caesarean. Animals were divided into 4 groups, viz. group lA (PGA+SCMC, n=12), IB (PGA, n=10), 2A (CC+SCMC, n= 10) and 2B (CC, n=9). Blood urea nitrogen (BUN), plasma creatinine and peritoneal fibrinogen concentrations in groups where PGA or CC was used along with SCMC decreased significantly, whereas total plasma proteins increased significantly during post-caesarean period. However, BUN, plasma creatinine and peritoneal fibrinogen concentrations increased significantly in animals where CC was used alone, whereas total plasma proteins decreased significantly during post-caesarean period compared to pre-caesarean concentrations. Increased concentrations of BUN, plasma creatinine and peritoneal fluid fibrinogen and decreased total plasma proteins over the passage of time following caesarean indicated severe inflammation, stress and protein catabolism in animals where CC was used alone compared to those where PGA or CC was used for suturing of uterine incision along with intra-peritoneal infusion of SCMC during caesarean.Â